Teacher attitudes towards managing inclusive classes in early childhood education level in Bulawayo central district primary schools in Bulawayo, Zimbabwe - Muverengi, Patience R. (Midlands State University, 2019)
This research sought to investigate teacher attitudes towards managing inclusive classes at Early Childhood Development Level in Bulawayo Central District Primary Schools. This was prompted by remarks given by teachers during gatherings, workshops and meetings. The researcher employed the descriptive survey design during the study. Data was generated through the use of questionnaires and interviews for classroom practitioners and Teachers in Charge (TICs). The sample comprised of thirty-five classroom practitioners and three TICs. Random sampling technique was done. The study established that teachers do have negative attitudes towards managing inclusive classes. Lack of expertise, lack of experience, lack of support from the school administrative staff, lack of adequate resources as well as large class size proved to be some of the factors that contribute to teachers’ negative attitudes towards managing inclusive classes at ECE level in Bulawayo Central District Primary Schools. The study recommends compulsory training in Special Needs Education in all teacher training colleges, the school administrative staff to support teachers in matters concerning inclusive education, enrolment of the number of learners as stipulated by policy per class and application for resources from donors, well-wishers, churches charity organisations and Non-Governmental Organisations by the government and the schools’ administrative staff.